Long-term outcome of nevirapine or efavirenz based antiretroviral regimens in mothers exposed to single dose nevirapine - Sripan,P. (Chiang Mai University, 2015)
Exposure to single dose nevirapine during labor (SD-NVP) to prevent mother to child transmission of HIV (PMTCT) is associated with a lower likelihood of virologic suppression at six months of a nevirapine based antiretroviral therapy but long-term consequences of SD-NVP have not been studied. We analyzed data from women who received SD-NVP in the PHPT-2 PMTCT clinical trial. Following delivery, women initiated a regimen composed of nevirapine, lamivudine, and stavudine or zidovudine when their CD4 level declined to less than 250 cells/mm3. HIV RNA load and CD4 cell counts were evaluated every six months. Failure was defined as a confirmed HIV RNA load >400 copies/mL at least 6 months after therapy initiation, or death, and observations were censored at time of drop out or switch to a protease inhibitor based regimen. Survival analysis was performed using Kaplan-Meier estimates and Cox regression models. The 221 SD-NVP exposed women and 48 unexposed women had similar characteristics at baseline, except the time spent between delivery and initiation of therapy (6.1 and 14.9 months, respectively). At four years, 35% of the SD-NVP exposed and 14% of the unexposed women met the failure criteria (P=0.02). In the multivariable analysis, factors contributing to the failure consisted of exposure to SD-NVP (HR: 2.63, P=0.03), plasma HIV-1 RNA level above median (HR: 2.53, P<0.001), stage C of the CDC HIV clinical staging (HR: 2.12, P=0.04), platelets cell count above median (HR: 1.65, P=0.04) and early initiation of therapy after delivery (HR: 1.64, P=0.04). In this cohort, the impact of SD-NVP on further antiretroviral therapy was still significant after four years of therapy, justifying the use of strategies to prevent resistance mutations after exposure to SD-NVP.